Pleural Mesothelioma: Unexpected Finding in a Young Man - Ullah, Raza; Khan, Imranullah; Naz, Shahida; Ahmad, Aamir; Haleema (Journal of Gandhara Medical and Dental Science, 2022)
Pleural mesothelioma is the disease of the elderly, usually in the seventh decade of life. Asbestos exposure is the most common finding among these patients. Other causes include a simian virus, radiation exposure, genetic predisposition and erionite. Common symptoms include shortness of breath, weight loss, dull achy chest pain on the site of the lesion and anorexia. Pleural effusion is common and video-assisted thoracoscopic (VATS) biopsy is the investigation of choice. pleurectomy, pleuro-pneumonectomy and cisplatin-based therapy are management modalities depending upon the stage of the disease. We are presenting an unusual case of pleural mesothelioma in a young patient with no significant exposure to the causative agent.